1984
DOI: 10.1287/mnsc.30.6.720
|View full text |Cite
|
Sign up to set email alerts
|

A Quantity Discount Pricing Model to Increase Vendor Profits

Abstract: In this paper, we analyze how a supplier can structure the terms of an optimal quantity discount schedule. The vendor's challenge is to adjust his present pricing schedule to entice his major customer to increase his present order size by a factor of "K." Optimal levels for "K" and the corresponding price discount are determined in order to maximize the supplier's incremental net profit and cash flow. Implementation issues are discussed and future research needs identified.inventory/production: policies, prici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
202
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(204 citation statements)
references
References 4 publications
1
202
1
Order By: Relevance
“…A supplier naturally wishes the opposite-he would like to see the retailer buy the material in advance and keep a large inventory to meet the fluctuations in external demand. One of the traditional tools that suppliers have employed to entice retailers in this direction is to offer quantity discounts (Monahan 1984).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A supplier naturally wishes the opposite-he would like to see the retailer buy the material in advance and keep a large inventory to meet the fluctuations in external demand. One of the traditional tools that suppliers have employed to entice retailers in this direction is to offer quantity discounts (Monahan 1984).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering the quantity discount of direct material, this paper divided the material purchase discount pricing into high, medium and low degree levels [70,71]. This study used three segments of piecewise linear function, as shown in Figure 5.…”
Section: Sensitivity Analysis Of the Quantity Discount Of Direct Matementioning
confidence: 99%
“…This model has received substantial attention in the literature, and assumes a number of different forms. In particular, Monahan (1984) has referred to a setting with a single purchaser that meets demand for a single product occurring at a constant rate, while ordering the product from a vendor who operates in the lot-for-lot fashion. In this setting, the vendor's quantity discounts were used as the means of coordination.…”
Section: Introductionmentioning
confidence: 99%